92.2k views
1 vote
SOLUTION We observe that f '(x) = -1 / (1 + x2) and find the required series by integrating the power series for -1 / (1 + x2).

1 Answer

4 votes

Answer:

Required series is:


\int{(-1)/(1+x^(2)) \, dx =-x+(x^(3))/(3)-(x^(5))/(5)+(x^(7))/(7)+.....

Explanation:

Given that


f'(x) = -(1)/(1 + x^(2)) ---(1)

We know that:


(d)/(dx)(tan^(-1)x)=(1)/(1+x^(2)) ---(2)

Comparing (1) and (2)


f'(x)=-(tan^(-1)x) ---- (3)

Using power series expansion for
tan^(-1)x


f'(x)=-tan^(-1)x=-\int {(1)/(1+x^(2)) \, dx


= -\int{ \sum\limits^( \infty)_(n=0) (-1)^(n)x^(2n)} \, dx


= -\sum{ \int\limits^( \infty)_(n=0) (-1)^(n)x^(2n)} \, dx


=-[c+\sum\limits^( \infty)_(n=0) (-1)^(n)(x^(2n+1))/(2n+1)]


=C+\sum\limits^( \infty)_(n=0) (-1)^(n+1)(x^(2n+1))/(2n+1)


=C-x+(x^(3))/(3)-(x^(5))/(5)+(x^(7))/(7)+.....

as


tan^(-1)(0)=0 \implies C=0

Hence,


\int{(-1)/(1+x^(2)) \, dx =-x+(x^(3))/(3)-(x^(5))/(5)+(x^(7))/(7)+.....

User Norbert Huurnink
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.